Development of contactless cauterization device for surgery using a steam-jet - Yoshiki, Hitoshi; Tadano, Kotaro; Ban, Daisuke; Ohuchi, Katsuhiro; Tanabe, Minoru; Kawashima, Kenji (British Journal of Healthcare and Medical Research, 2016)
To improve outcomes in surgery, surgical energy devices which perform coagulation and cauterization with shorter operating time, less thermal injury, and less adherence are required. In this paper, basic principles and cauterization mechanisms of cauterization method with steam-jet were studied. The steam-jet coagulator (SJC) was newly developed with dry-steam generator for effective heat-transfer with steam. The condensation heat-transfer coefficient at the surface was estimated through thermofluidic simulations and experimental temperature distributions inside the heated object by impinging steam-jet. The steam-jet of 10kPa(G) and 30kPa(G) were estimated to have the heat-transfer coefficients larger than 5.0×105 W/m2 under several design parameters. Histological images of coagulated hepatic tissues with the SJC, the bipolar electrocautery device, and the bipolar with the saline irrigation method were compared. The comparison revealed that steam-jet can coagulate tissue denser and can seal sinusoids better than the ones coagulated with the bipolar electrocautery device even if the saline irrigation method was used. Successful coagulation and cauterization were performed on the in-vivo experiment using porcine liver, and thus the feasibility of the proposed method was confirmed. Our findings represent the engineering principles, the histological mechanisms, and the feasibility in in-vivo situations of the contactless cauterization device using a steam-jet.